Effectiveness of Satpol PP and WH Performance in Controlling Civil Servants Based on Aceh Governor Regulation Number 139 of 2016 in Aceh Besar [Efektivitas Kinerja Satpol PP dan WH dalam Penertiban PNS Menurut Pergub Aceh Nomor 139 Tahun 2016: Studi Kasus di Kabupaten Aceh Besar] - Safira Maulina; Khairani Khairani; Rispalman Rispalman (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2020)
Abstract: This paper is to answer the problem of the effectiveness of the performance of the Civil Service Police Unit and the Wilayatul Hisbah in controlling civil servants according to Aceh Governor Regulation number 139 of 2j016. Ideally, Satpol PP and WH are required to carry out their duties and authorities in controlling civil servants who are negligent during office hours and staff. Civil servants are required to comply with the regulations set out in the civil servant code of ethics and if not implemented, they will be subject to disciplinary punishment, whether it is a light, moderate or severe level of disciplinary punishment according to the violation. The formulation of the problem is first, how are the performance of Satpol PP and WH in controlling civil servants in Aceh Besar. Second, how the strategies implemented by the Satpol PP and WH in controlling civil servants in Aceh Besar have been implemented effectively. Third, how is the review of Islamic law on the implementation of controlling civil servants? This research was conducted using an empirical normative legal approach using the type of field research (Field Research) and literature (Library Research), namely reviewing written law as well as facts in the field using analytical descriptive patterns to describe or provide an overview of the object under study through data or samples collected. have been collected by concluding. From the results of the study, it was found that the Aceh governor regulation number 139 of 2016 has regulated the control of civil servants who leave without permission during office hours and the law of each violator has been regulated in the civil servant code of ethics itself. Satpol PP and WH are not fully effective in carrying out their duties because there are still many employees who are outside as well as the strategies to overcome obstacles that are carried out are also ineffective. Abstrak: Kajian ini untuk menjawab permasalahan efektivitas kinerja Satuan Polisi Pamong Praja dan Wilayatul Hisbah dalam penertiban pegawai negeri sipil menurut peraturan gubernur Aceh nomor 139 tahun 2016 tentang kedudukan, susunan organisasi, tugas, fungsi dan tata kerja satuan Pamong Praja dan Wilayatul Hisbah Aceh . Idealnya, Satpol PP dan WH wajib melaksanakan tugas dan wewenangnya dalam penertiban PNS yang lalai pada saat jam dinas dan para PNS wajib menaati peraturan yang telah ditetapkan dalam kode etik PNS dan apabila tidak dilaksanakan akan dikenakan hukuman disiplin baik itu hukuman disiplin tingkat ringan, sedang ataupun berat sesuai dengan pelanggaran. Rumusan masalahnya ialah pertama, Bagaimana Kinerja Satpol PP dan WH dalam penertiban PNS di Aceh besar. Kedua, Bagaimana strategi yang dijalankan oleh Satpol PP dan WH dalam penertiban PNS di Aceh besar sudah dilaksanakan secara efektif. Ketiga, Bagaimana tinjauan hukum Islam terhadap pelaksanaan penertiban PNS. Penelitian ini dilakukan menggunakan pendekatan hukum normatif empiris menggunakan jenis penelitian lapangan (Field Research) dan kepustakaan (Library Research) yakni mengkaji hukum yang tertulis juga fakta di lapangan dengan menggunakan pola deskriptif analitik untuk mendeskripsikan atau memberi gambaran terhadap objek yang diteliti melalui data atau sampel yang telah terkumpul dengan membuat kesimpulan. Dari hasil penelitian didapati bahwa dalam peraturan gubernur Aceh nomor 139 tahun 2016 telah mengatur penertiban terhadap PNS yang keluar tanpa izin pada saat jam dinas dan hukum setiap pelanggar telah diatur dalam kode etik PNS sendiri. Satpol PP dan WH tidak sepenuhnya efektif melaksanakan tugas karena masih banyak pegawai yang berada diluar begitupun dengan strategi untuk mengatasi hambatan yang dilakukan juga tidak efektif.